Ethnography of Communication: The Analysis of Dell Hymes’ SPEAKING Model in the Communication among the Infertility Husband and Wife - Ketut Ari Setyawati (Pusat Studi Bahasa dan Publikasi Ilmiah, 2022)
The present study was employed qualitative descriptive methods to examine ethnography of communication using Dell Hymes’ SPEAKING mnemonic in the communication between husband and in wife who has no children for a long time in their family. the findings showed a connection between a childless couple with Hymes’ SPEAKING terms. The results were communication among husband and wife who get infertility took place in the couple’s house particularly in the living room (Setting) in which the scenes were a debate between husband and wife (Participants) who sat opposite in the night (Scene) to seek a corporate solution and maintain the relationship (Ends). The Act was started by awkward conversations which trigger argument and lead to quarrel (A). There were several tones such as serious, tense, sad, promised, regret, apologize, anger, mocking, rude, and pleading in which the communication was conducted in verbal and non-verbal speech (Key) by including code-mixing (Instrumentalities). The husband and wife communicated alternately as speaker and hearer who asking and questioning to respect each other and understanding each situation (Norms of interaction and interpretation). The genre was quarrel as the dialogues were about the debate (Genre).